TRANSCRIPTION FACTORS OF EMBRYONIC STEM CELLS AND INDUCED PLURIPOTENT STEM CELLS - Aquino Ordinola, Ruth (2015)
Since their therapeutic potential was discovered, stem cells with pluripotent capacity have been sought, and since then embryonic stem cells (ESCs) became an important center in stem cell-basedtherapy, there are ethical problems with the use of embryos. Using a small group of transcription factors (c-Myc, Oct4, Klf4 and Sox-2), fibroblasts in pluripotent stem cells (iPSC) were converted. This stem cell technology currently has some disadvantages, because there are differences in gene expression profiles due to retention of an "epigenetic memory" from the cells from which they were derived; this could cause problems when applying them in therapy. In this review we discuss the role of some transcription factors involved in iPSCs and ESCs.